SOCIAL CONTROL OF MISBEHAVIOR AMONG MUSLIM YOUTH IN BIMA DISTRICT, INDONESIA - Arlin Adam; Irman Susanto; Zainuddin Zainuddin (Universitas Islam Negeri Alauddin Makassar, 2018)
The main objectives of this study is to find out the mechanisms of social control are less able to control the deviant behavior of adolescents. Another thing might to be considered is to find out social control over juvenile deviant behavior. This study employs a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The research suggest that the mechanism of social control carried out by the police, religious leaders, traditional leaders, educator figures, community leaders and parents in controlling adolescent deviant behavior was relatively low in the form of social control in the form of persuasive and repressive actions. In addition, there is no form of cooperation between the government, the police and the community in controlling juvenile deviant behavior. Social control carried out by the police, religious leaders, traditional leaders, educator figures, community leaders and parents on the deviant behavior of adolescents in Monta Subdistrict, Bima Regency starts from coaching, socialization and reprimand. The social control mechanism that we can apply in adolescent deviant behavior is the cooperation of the government and the community in controlling juvenile deviant behavior